Untangling Africa's peace and growth trajectories: The role of property rights - Martins Iyoboyi; Muftau Olaiya Olarinde (Journal of Government and Economics (JGE), 2025)
The role of government in promoting property rights has been acknowledged in the literature. This study investigates the impact of property rights peace, and consequently the impact of peace and property rights on economic growth, utilizing the system Generalized Method of Moments technique on panel data on 31 African countries from 2008 to 2019. The results indicate that the institutional structure in natural resource-based countries, through mitigating the effects of the natural resource curse phenomenon, improves economic growth. The paper concludes with actionable recommendations on the contributions of property rights on peace and economic growth and recommends policies that improve the quality of property rights in the African context and government integrity. The role of government is critical in Africa, in ensuring improved property rights and ensuring a peaceful environment for growth.
Keywords: 330; Africa; Economic growth; Peace; Property rights; System GMM